Cyclic microwave assisted synthesis of Sb 2S 3 twin flowers in solutions containing a template and splitting agent - Kavinchan J. (2017)
Antimony sulfide (Sb 2 S 3 ) was successfully synthesized from antimony chloride (SbCl 3 ) and sodium thiosulfate (Na 2 S 2 O 3 ) in ethylene glycol (EG) containing different contents of cetyltrimethylammonium bromide (CTAB) as a template and splitting agent by the 600 W cyclic microwave radiation (CMR). X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and photoluminescence (PL) spectroscopy revealed the presence of only orthorhombic Sb 2 S 3 phase in the shape of twin flowers of single crystalline square nanorod petals, growing along the [001] direction, including the vibration peaks that were in accordance with those of the stibnite with the 435 nm violet wavelength emission peaks.